Carvacrol Arrests the Proliferation of Hypopharyngeal Carcinoma Cells by Suppressing Ornithine Decarboxylase and Hyaluronidase Activities - Fatima, Kaneez; Luqman, Suaib; Meena, Abha (Frontiers in Nutrition, 2022)
Carvacrol, a monoterpene known for its pharmacological activities, is present in the essential oil of Origanum majorana, Origanum vulgare, Thymus vulgaris, and Lippia graveolens. It is used in food as a flavoring and preservative agent in cosmetics and medicines because of its useful bioactivities in clinical practice. However, carvacrol was not much explored for its anticancer potential. Targeting enzymes involved in carcinogenesis, such as ornithine decarboxylase (ODC), cyclooxygenase-2 (COX-2), lipoxygenase-5 (LOX-5), and hyaluronidase (HYAL) by monoterpenes are amongst the efficient approaches for cancer prevention and treatment. In this study, the efficacy of carvacrol was investigated against deregulated cancer biomarkers/targets in organ-specific human cancer cell lines (FaDu, K562, and A549) utilizing in vitro, in silico, and in vivo approaches. The efficacy of carvacrol was evaluated on human cancer cell lines using neutral red uptake (NRU), sulpho rhodamine B (SRB), and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays. The mechanistic study was carried out in cell-based test systems. Further, the potency of carvacrol was confirmed by the quantitative real-time PCR analysis and molecular docking studies. The in vivo anti-tumor potential of carvacrol was performed on mice S-180 model, and the toxicity examination was accomplished through in silico approach. Carvacrol significantly impeded the growth of FaDu, K562, and A549 cell lines with IC50 values ranging from 9.61 ± 0.05 to 81.32 ± 11.83 μM. Further, the efficacy of carvacrol was explored against different cancer targets in FaDu, K562, and A549 cell lines. Carvacrol inhibits the ODC, COX-2, LOX-5, and HYAL activities in FaDu cell line and ODC, COX-2, and HYAL activities in K562 cell line. The results were validated by expression analysis revealing the downregulation of the targeted gene with a significant change in the transcript level of ODC and HYAL in FaDu cell line with a fold change of 1.56 and 1.61, respectively. A non-significant effect of carvacrol was observed on the downstream signaling pathway of PI3K and HIF-1α/vascular endothelial growth factor (VEGF) in FaDu cells. The cell cycle, reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and Annexin V-fluorescein isothiocyanate (FITC) experiments demonstrate that carvacrol induces apoptosis of FaDu cells. Further, the potency of carvacrol was also evaluated in vivo on mice S-180 tumor model, wherein it inhibits tumor growth (72%) at 75 mg/kg body weight (bw). ADMET studies predicted carvacrol as a safe molecule. Overall, carvacrol delayed the growth of FaDu, K562, and A549 cell lines by targeting enzymes involved in the carcinogenesis process. The existence of one hydroxyl group at the para position of carvacrol could be responsible for the anti-proliferative activity. Thus, carvacrol could be used as a pharmacophore to develop a safe and effective multi-targeted anti-cancer medicament.